2016
DOI: 10.1007/s13762-016-1095-z
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical background of potentially toxic trace elements in reclaimed soils of the abandoned pyrite–uranium mine (south-central Poland)

Abstract: Spatial distribution patterns of As, Ba, Cd, Cr, Cu, Mn, Ni, Pb, U and Zn were determined in topsoil samples collected after 40 years of chemical remediation conducted in the inoperative ''Staszic'' pyrite-uranium mine in the Holy Cross Mountains, south-central Poland. Soil samples were taken from 58 sites using a systematic random sampling design. Selected samples were subjected to an X-ray diffractometry analysis on bulk soils and separated clay fractions. Hematite, goethite and gypsum are common mineral pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Abandoned mining areas belong to the most dangerous uncontrolled sources of pollutants (Kim and Hyun 2015). For several years, these areas have gained significant attention to scientific community (Bori et al 2016; Bosso and Enzweiler 2008; Castillo et al 2013; Gałuszka et al 2016; Sheoran et al 2010; Xu et al 2017). This is not surprising, given the fact that many of them have not been submitted to the recovery program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abandoned mining areas belong to the most dangerous uncontrolled sources of pollutants (Kim and Hyun 2015). For several years, these areas have gained significant attention to scientific community (Bori et al 2016; Bosso and Enzweiler 2008; Castillo et al 2013; Gałuszka et al 2016; Sheoran et al 2010; Xu et al 2017). This is not surprising, given the fact that many of them have not been submitted to the recovery program.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of abandoned mining areas carried out in the Holy Cross Mountains (HCM) (Gałuszka et al 2018, 2016, 2015; Migaszewski et al 2015; Uzarowicz 2011) reported high levels of some trace elements in examined soils and their high heterogeneity (Dołęgowska et al 2015). As documented by Gałuszka et al (2016, 2015), most of the elements examined (e.g., As, Cd, Cu, Pb, and U) showed higher mean contents than recommended standard values for soils in protected areas of Poland, but concurrently, they were lower than those noted in soils of industrial areas. Of the wide range of elements determined, no studies have been conducted on mercury which is regarded as a highly toxic element, and its concentrations in surface soil horizons can be a potential threat to terrestrial organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the concept of geochemical background values was proposed as a tool for evaluating environmental quality, predicting contaminant transport and transformation of the area, monitoring environmental pollution, and determining the content of chemical elements in the natural environment [1][2][3]. Geochemical background values have since been applied widely in the field of environmental evaluation to describe the differences between element concentrations derived from nature and concentration anomalies derived from human activity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Because they are not biodegradable (Habiba et al, 2015;Bandara et al, 2017), and restrict the opportunities for future land use. Geogenic and anthropogenic activities are the major sources of PTEs particularly As, Cd, Pb, Cr and Ni globally (Pratas et al, 2013;Galuszka et al, 2016). In China, rapid economic development and industrialization in most coastal areas has led to elevated concentrations of PTEs (particularly Ni, Cr, As, Cd and Pb) in arable fields (Khan et al, 2014;Ibrahim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%